The legal treatment of inefficiency in the unilateral disposition of goods in the marital partnership at the gates of the Eighth Civil Cassation Plenaries - Vargas Jiménez, Marja Ulanova (2018)
The main object of this research is to analyze the ideal legal consequence in the acts of disposition or encumbrance of property of the marital partnership carried out by one of the consorts who is registered in the Public Records as if they were property of the conjugal. Developed in the debates at the gates of issuing the Eighth Civil Cassation Plenaries, it is important to establish if the legal remedy is the nullity or inefficacy of the legal business held by the spouse who does not have a special power of the other consort to represent society.